Molecular Modeling of Structures and Interaction of Human Corticotropin-Releasing Factor (CRF) Binding Protein and CRF Type-2 Receptor - Slater, Paula G.; Gutierrez-Maldonado, Sebastian E.; Gysling, Katia; Lagos, Carlos F. (Frontiers in Endocrinology, 2018)
The corticotropin releasing factor (CRF) system is a key mediator of the stress response and addictive behavior. The CRF system includes four peptides: CRF, Urocortins I-III, a protein that binds CRF with high affinity (CRF-BP), and two class-B G-protein coupled receptors CRF1R and CRF2R. CRF-BP is a secreted protein without significant sequence homology to CRF receptors or to any other known class of protein. Recently, it has been described a potentiation role of CRF-BP over CRF signaling through CRF2R in addictive related neuronal plasticity and behavior. In addition, it has been described that CRF-BP is capable of physically interact specifically with the α isoform of CRF2R and acts like an escort protein increasing the amount of the receptor in the plasma membrane. At present, there are no available structures for CRF-BP or for full-length CRFR. Knowing and studying the structure of these proteins could be beneficial in order to characterize the CRF-BP/CRF2αR interaction. In this work, we report the modeling of CRF-BP and of full-length CRF2αR and CRF2βR based on the recently solved crystal structures of the transmembrane domains of the human glucagon receptor and human CRF1R, in addition with the resolved N-terminal extracellular domain of CRFRs. These models were further studied using molecular dynamics simulations and protein-protein docking. The results predicted a higher possibility of interaction of CRF-BP with CRF2αR than CRF2βR, and yielded the possible residues conforming the interacting interface. Thus, the present study provides a framework for further investigation of the CRF-BP/CRF2αR interaction.